Analysis of Factors Affecting Seafarer Satisfaction in Online Seaman's Book Issuance Services at the Tanjungwangi Class III KSOP Office - Frandy Irawan; Hary Sulaksono; Muhaimin Dimyati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Analysis of Factors Affecting Sailors' Satisfaction in the Online Seafarer Book Issuance Service at the KSOP Class III Tanjung Wangi Office. This study analyzes the factors that influence sailors' satisfaction in the Online Seafarer Book issuance service at the KSOP Class III Tanjung Wangi Office. The aim of this research is to explore the impact of Service Quality, Ease of Use, and Data Security, both individually and collectively, on ship operators' satisfaction. The method used is a quantitative approach with multiple linear regression analysis on data obtained through questionnaires. Although the hypothesis suggested an expected simultaneous relationship between the independent variables (Ease of Use, Service Quality, and Data Security) and the dependent variable (Sailors' Satisfaction), the research findings indicate that this relationship did not materialize. These findings require further analysis to identify factors that may have caused the discrepancy in results, such as the presence of unaccounted variables or the use of an inappropriate analytical model.